1994
DOI: 10.1021/om00019a021
|View full text |Cite
|
Sign up to set email alerts
|

The Remarkable Photochemistry of fac-XMn(CO)3(.alpha.-diimine) (X =Halide): Formation of Mn2(CO)6(.alpha.-diimine)2 via the mer Isomer and Photocatalytic Substitution of X- in the Presence of PR3

Abstract: The remarkable photochemistry of fac-XMn(CO)sub3(alpha-diimine) (X=halide). Formation of Mnsub2(CO)sub6(alpha-diimine)sub2 via the mer-isomer and photocatalytic disproportionation in the presence of PRsub3 Stor, G.J.; Morrison, S.L.; Stufkens, D.J.; Oskam, A. Published in: Organometallics DOI:10.1021/om00019a021Link to publication Citation for published version (APA):Stor, G. J., Morrison, S. L., Stufkens, D. J., & Oskam, A. (1994). The remarkable photochemistry of facXMn(CO)sub3(alpha-diimine) (X=halide). For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 0 publications
10
120
0
1
Order By: Relevance
“…This behavior is similar to that reported for the symmetric non-aromatic Mn R-DAB (R = alkyl) compounds. 8,30 The formation of a stable bicarbonate complex, either through the coordination to the metal center or via the imino C=N bond 23,37 leads to the need of increased overpotential. From that point of view, the steric hindering (protection) of the metal center/the imino C=N bond in the Mn(IP) complexes is advantageous as it disfavors the Mn Mn dimerization (when comparing MnIMP with MnDIPIMP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior is similar to that reported for the symmetric non-aromatic Mn R-DAB (R = alkyl) compounds. 8,30 The formation of a stable bicarbonate complex, either through the coordination to the metal center or via the imino C=N bond 23,37 leads to the need of increased overpotential. From that point of view, the steric hindering (protection) of the metal center/the imino C=N bond in the Mn(IP) complexes is advantageous as it disfavors the Mn Mn dimerization (when comparing MnIMP with MnDIPIMP).…”
Section: Discussionmentioning
confidence: 99%
“…23 Indeed, it has recently been shown that the use of bipyridines incorporating bulky groups in the 6,6 -positions 24,25 (or, another bulkier heterocyclic ligand 26 ) largely inhibits dimerization in the catalytic cycle. The result is the formation of the stable 5-coordinate anion via the two-electron transfer (ECE) at the first cathodic wave.…”
Section: Abstract: Manganese Tricarbonyl Bromide Complexes Incorporatmentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation into these transitions gives rise to homolysis of the metal-metal or metal-alkyl bond and/or release of CO [1,8]. Release of CO has been observed only for the complexes [L,M-Mn(CO)3(a-diimine)] [12,13]; this reaction probably occurs from a low-lying LF state, since it was also observed for the corresponding halide complexes [Mn(X)(CO)3(a-diimine) ] [14]. The homolysis reactions, previously studied in detail for the above-mentioned metal-metal-bonded complexes [L,M-M'(CO)3(a-diimine)] [1][2][3][4][5][6], proceeded with very high quantum yields (0.3-0.9).…”
Section: Introductionmentioning
confidence: 99%
“…9 Such a mechanism would explain, for instance, formation of the CO back reaction product of mer-MnCl(CO) 3 (R-diimine) after irradiation of the corresponding fac isomer. 14 Upon UV excitation of transition metal carbonyl complexes, a greater amount of energy is deposited into the reacting molecule than is needed to dissociate the metal-CO bond. In the process, part of the excess energy is transformed into translational energy of the dissociating carbonyl group, and the rest is converted into heat via intramolecular vibrational redistribution, which finally is dissipated into the solvent.…”
Section: Introductionmentioning
confidence: 99%